Isolation and partial characterization of a new strain of Klebsiella pneumoniae capable of high 1,3 propanediol production from glycerol - B. Sen; A.P. Dabir; V.B. Lanjekar; D.R. Ranade (Global Journal of Environmental Science and Management)
Glycerol is a promising feedstock for microbial cultivation and production of 1,3 propanediol (1,3 PDO). Here we report a newly isolated bacterial strain BA11 from soil, capable of fermenting glycerol to 1,3 PDO, and has been identified to be a strain of Klebsiella pneumoniae. Strain BA11 was fast growing showing peak 1,3 PDO production in 6 h of cultivation with productivity of 1.2 g/L-h without the addition of Vitamin B12. Based on the optimum glycerol utilization (75%) and 1,3 PDO production (8.3 g/L) and yield (0.56 mol/mol glycerol utilized), the most appropriate glycerol concentration for cultivation was 20 g/L. The strain BA11 could tolerate the pH range of 6 to 8.5 as no inhibitory effects were seen on growth as well as 1,3 PDO production. Strain BA11 was most active and could produce high 1,3 PDO in the incubation temperature range of 25 to 40 oC. The production of 1,3 PDO was maximum (9.3 g/L) under aerobic condition with 95.8% glycerol utilization. Addition of glucose to the glycerol fermentation led to increased cell mass but no improvement in the 1,3 PDO production.